2011
DOI: 10.1111/j.1365-2125.2010.03869.x
|View full text |Cite
|
Sign up to set email alerts
|

The potent calcitonin gene‐related peptide receptor antagonist, telcagepant, does not affect nitroglycerin‐induced vasodilation in healthy men

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT WHAT THIS STUDY ADDS• This study shows that telcagepant, at a supra-therapeutic dose for the treatment of acute migraine headache, has no clinically relevant effect on NTG-induced haemodynamic changes in healthy male volunteers. There is also no measurable vasoconstrictor effect of telcagepant as such in both the central and peripheral vascular bed. The results of the present study support the favourable cardiovascular safety profile of telcagepant and indicate that CGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 48 publications
3
22
1
Order By: Relevance
“…The present findings are in line with preclinical data, 10‐15 and findings in healthy human subjects 16‐18 suggesting that CGRP receptor antagonism does not have direct vasoconstrictive effects. There are a number of limitations to the interpretation of the present data.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present findings are in line with preclinical data, 10‐15 and findings in healthy human subjects 16‐18 suggesting that CGRP receptor antagonism does not have direct vasoconstrictive effects. There are a number of limitations to the interpretation of the present data.…”
Section: Discussionsupporting
confidence: 92%
“…In dogs, CGRP 8‐37 did not influence hemodynamics after induction of congestive heart failure, 13 the severity of myocardial ischemia, 14 or the reactive hyperemic response to brief coronary occlusion 15 . In healthy humans, telcagepant had no effect on peripheral hemodynamics, 16 24‐hour mean ambulatory blood pressure and heart rate, 17 or nitroglycerin‐induced vasolidation 18 . Thus, antagonism of CGRP may potentially allow for treatment of migraine in patients with coronary artery disease.…”
mentioning
confidence: 99%
“…The BAD fold increase following NTG was 1.14 after telcagepant vs 1.13 after placebo. No vasoconstrictor effect of telcagepant could be demonstrated …”
Section: What Are the Cardiovascular Consequences Of Inhibiting Cgrp mentioning
confidence: 94%
“…Early human experiments were conducted by Petersen and colleagues, who showed clinically that low doses of the CGRP‐RA olcegepant completely inhibited headache induced by CGRP, yet at supratherapeutic doses there was no effect on blood pressure, the diameter of systemic or cerebral arteries, or cerebral blood flow . Clinically, studies with telcagepant (MK‐0974) showed that it had no effect on spontaneous ischemia in cardiovascular patients, that it did not affect exercise time at supratherapeutic doses in patients with stable angina, that it did not affect nitroglycerin‐induced vasodilation in healthy men, nor was there any hemodynamic interaction with sumatriptan . A partially completed study of supratherapeutic doses of telcagepant (600 and 900 mg) in patients with migraine and stable coronary artery disease also supported the cardiovascular safety of the CGRP receptor antagonist mechanism …”
Section: Safety and Tolerability Of The Cgrp Antibodiesmentioning
confidence: 99%